Effects of transcranial alternating current stimulation on neurophysiologic motor function in Parkinson’s patients: a systematic review and meta-analysis - Ye, Fangcheng; Shao, Yinjin; Wu, Guihua; Huang, Miao; Huang, Hui (Frontiers in Aging Neuroscience, 2025)
ObjectiveThis systematic review and meta-analysis aimed to evaluate whether tACS improves neurophysiologic motor function in patients with Parkinson’s patients.MethodsWe searched PubMed, Embase, Web of Science, and Cochrane Library for eligible studies from inception to March 2025. Measured outcomes included two indicators of neurophysiologic function: motor evoked potentials and short-term intracortical inhibition. The Cochrane risk of bias tool was used to evaluate the quality of the included literature, and extracted data were qualitatively synthesized and meta-analyzed.ResultsOut of the 145 studies identified from the electronic databases, 7 fulfilled the inclusion criteria. Our results indicate that tACS significantly improved motor function in patients with PD compared to patients without tACS treatment. Motor function was assessed using motor evoked potentials (standardized mean deviation [SMD] = 2.65; 95% confidence interval [CI] = 2.02 to 3.27, I2 = 39%, p < 0.00001) and short-interval intracortical inhibition (SMD = 1.88; 95% CI = 1.47 to 2.30, I2 = 47%, p < 0.00001).ConclusionOur findings suggested that tACS was strongly associated with improvements in motor evoked potentials and short-interval intracortical inhibition and could significantly improve neuromotor function. The results of this study provide additional evidence for the effectiveness of tACS and encourage the use of tACS in PD rehabilitation in clinical practice.Systematic review registrationThe study protocol is registered with the International Prospective Register of Systematic Reviews under the registration number CRD420251016245.